Proximity/distance at the meeting on “the other side” - Петреска, Весна (Poznańskie Studia Slawistyczne, 2012)
Folk  healers  and  their  ability  to  heal  can  be  connected  with  death  or  the  being  owned  by death. This deeply archaic structure is evident in how knowledge is acquired, namely that it is passed on from mother to daughter or granddaughter/grandson in a place that suggests a connection to the other world (water, bridge). It is also evident in the fact that the women performing charms must be postmenopausal. Also important is the fact that when knowledge is acquired through dreams and visions, the soul of the initiate or the initiate him- or herself must be in touch with the other world and then return to life by passing over a thin line: a bridge as wide as a hair or a straw. This is a condition akin to death followed by eventual recuperation.  Another  important  point  is  the difference  in  physical  appearance  to  those treated, for example, old, white, a pale face, piercing eyes, small, slouching, etc. All these incorporate  the  idea  that  the  communication  with  the “other world”,  “the  other  side”,  is always given to those people that somehow were in touch with the other world, which from that perspective are far from us, but originating from our environment and transferring the message that they are also close to us. The connection with the other side, with the other, distanced world was also seen in the time-space structure on the charms.